Variables associated with extra uterine growth restriction in very low birth weight infants - Paola Azara Tabicas Lima; Manoel de Carvalho; Ana Carolina Carioca da Costa; Maria Elisabeth Lopes Moreira (Elsevier, 2014)
Objectives: to determine the rate of extrauterine growth restriction in very low birth weight infants and to evaluate the influence of perinatal variables, clinical practices, and neonatal morbidities on this outcome. Methods: a longitudinal study was performed in four neonatal units in the city of Rio de Janeiro. 570 very low birth weight infants were analyzed. The study included perinatal variables, variables related to clinical practices, and incident morbidities in these preterm infants. Extrauterine growth restriction was defined using z-scores for weight or head circumference ≤ -2 for corrected age. Statistical analysis was performed using the Statistical Package for Social Sciences (SPSS) and R software. Results: this study comprised 570 infants, of which 49% were males, and 33% were small for gestational age (SGA). The mean weight and head circumference at birth were 1,113 ± 267 g and 27 ± 2 cm, respectively. The mean z-scores of birth weight and weight at discharge were -0.96 ± 0.78 and -1.54 ± 0.75, respectively; for head circumference, the mean z-scores at birth and at discharge were -0.63 ± 1.18 and -0.45 ± 0.94, respectively. The rate of extrauterine growth restriction considering the weight was 26% (149/570) and considering the head circumference, 5% (29/570). SGA was the variable with the greatest impact on both growth restriction for weight (PR = 4.33) and for head circumference (PR = 2.11) in adjusted analyses. Conclusion: extrauterine growth restriction was high in the population, especially for SGA newborns and those with neonatal morbidities. Resumo: Objetivos: determinar a frequência da restrição de crescimento extrauterino em recém-nascidos pré-termos de muito baixo peso e avaliar o impacto de variáveis perinatais, práticas clínicas e morbidades neonatais nesta morbidade. Materiais e métodos: foi realizado um estudo longitudinal em 4 unidades neonatais do Rio de Janeiro. Foram analisados 570 recém-nascidos pré-termos de muito baixo peso. Foram incluídas no estudo variáveis perinatais, variáveis relacionadas às práticas clínicas e morbidades incidentes nestes recém-nascidos. A restrição de crescimento extrauterino foi definida pelos escores z de peso ou perímetro cefálico ≤ -2 para idade corrigida. Na análise estatística foram utilizados o software SPSS e o software R. Resultados: foram analisados 570 recém-nascidos dos quais 49% eram do sexo masculino e 33% nasceram pequenos para idade gestacional. A média do peso e perímetro cefálico ao nascimento foi respectivamente 1113 ± 267 g e 27 ± 2 cm. As médias de escore z do peso ao nascimento e na alta foram respectivamente, -0,96 ± 0,78 e -1,54 ± 0,75 e as do perímetro cefálico foram -0,63 ± 1,18 e -0,45 ± 0,94. A frequência de restrição de crescimento extrauterino considerando o peso foi 26% do perímetro cefálico foi de 5%. Nascer pequeno para idade gestacional foi a variável de maior impacto na restrição de crescimento tanto para o peso (RP 4,33) quanto para o perímetro cefálico (RP 2,11) nas analises ajustadas. Conclusão: a restrição de crescimento extrauterino foi alta na população, especialmente para os recém-nascidos PIG e com morbidades neonatais. Keywords: Premature, Growth, Malnutrition, Palavras-chave: Pematuro, Crescimento, Desnutrição